2014
DOI: 10.1159/000356522
|View full text |Cite
|
Sign up to set email alerts
|

FADD Is Upregulated in Relapsing Remitting Multiple Sclerosis

Abstract: Objective: To elucidate the role of tumor necrosis factor (TNF) receptor signal transduction in multiple sclerosis (MS). Methods: We performed a cross-sectional analysis of the gene expression of TNF receptor-associated death domain protein (TRADD) and Fas-associated death domain protein (FADD) in peripheral blood leukocytes of 23 relapsing remitting (RR), 19 secondary progressive (SP) and 12 primary progressive (PP) MS patients, as well as of 29 healthy controls by quantitative RT-PCR. Additionally, we monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Finally, the Fas-associated death domain protein (Fadd) ( = 0.41) is a molecule that interacts with various cell surface receptors and can be activated by members of the tumor necrosis factor receptor family to transmit apoptotic signals [ 59 ]. An increased expression of FADD was found in peripheral blood leukocytes of RR-MS patients highlighting an elevated general pro-inflammatory activity [ 60 ]. The increased Fadd regulation has also been observed in the grey matter of MS patients compared to controls [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Fas-associated death domain protein (Fadd) ( = 0.41) is a molecule that interacts with various cell surface receptors and can be activated by members of the tumor necrosis factor receptor family to transmit apoptotic signals [ 59 ]. An increased expression of FADD was found in peripheral blood leukocytes of RR-MS patients highlighting an elevated general pro-inflammatory activity [ 60 ]. The increased Fadd regulation has also been observed in the grey matter of MS patients compared to controls [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNFα adapter proteins ↑ FADD mRNA in leukocytes [66] ↑TRAF2 mRNA in leukocytes [67] ↓TRADD, FADD, RIP-1, TRAF-2 mRNA in PBMC [123] expression. Some kinds of dysregulation in cell functioning can be common in different autoimmune diseases.…”
Section: Smad7mentioning
confidence: 99%
“…TNFα signal transduction in lymphocytes is altered in multiple sclerosis. Fas-associated death domain protein (FADD) gene expression was upregulated in leukocytes from RRMS patients compared to SPMS, PPMS and healthy controls [66]. TRAF2 (TNF receptor-associated factor 2) gene expression was increased in leukocytes of RRMS patients compared to other MS forms and healthy controls.…”
Section: Tnfα and Il-17 Pathways In Multiple Sclerosismentioning
confidence: 99%
“…Rinta et al reported that the Fas-ligand was increased in the sera of RRMS patients during relapse [ 41 ]. In addition, the extrinsic pathway adaptor, FADD, was shown to be upregulated in RRMS individuals [ 42 ]. The switch from clinically isolated syndrome (CIS) to MS, in a cohort consisting of a limited number of patients, was associated with a different profile of apoptosis-related gene transcription in comparison with no converting CIS patients [ 43 ].…”
Section: Oligodendrocyte Apoptosis and Demyelinationmentioning
confidence: 99%